2022
DOI: 10.1016/j.amsu.2022.103315
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis in pediatric patients with Coronavirus Disease 2019 (COVID-19): A case series from a developing country's tertiary hospital

Abstract: Introduction and importance: A common gastrointestinal presentation of both COVID-19 and multisystem inflammatory syndrome in children (MIS-C) is acute abdominal pain, which sometimes mimics appendicitis. Literature describing children with COVID-19 infection and concurrent acute appendicitis is growing, and understanding these patients’ clinical picture is necessary for their proper treatment. Case presentation We present a case series of six healthy children before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As in the present case, Sturgill et al 21 presented a series of three children diagnosed with appendicitis and MIS-C related to SARS-CoV-2; all patients were initially admitted with a diagnosis of appendicitis and had an appendectomy before the further diagnosis of MIS-C. One and two cases from two-case series reported from South Africa and Indonesia, respectively, were treated nonsurgically and only received systemic antibiotics and antiviral medication. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the present case, Sturgill et al 21 presented a series of three children diagnosed with appendicitis and MIS-C related to SARS-CoV-2; all patients were initially admitted with a diagnosis of appendicitis and had an appendectomy before the further diagnosis of MIS-C. One and two cases from two-case series reported from South Africa and Indonesia, respectively, were treated nonsurgically and only received systemic antibiotics and antiviral medication. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…As in the present case, Sturgill et al 21 presented a series of three children diagnosed with appendicitis and MIS-C related to SARS-CoV-2; all patients were initially admitted with a diagnosis of appendicitis and had an appendectomy before the further diagnosis of MIS-C. One and two cases from two-case series reported from South Africa and Indonesia, respectively, were treated nonsurgically and only received systemic antibiotics and antiviral medication. 22,23 Tullie et al 24 presented a case series and highlighted that children with MIS-C associated with COVID-19 may exhibit clinical characteristics suggesting appendicitis. Using advanced radiological procedures, however, a differential diagnosis was made for the children in the London series, and operative intervention was subsequently abounded.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review revealed that 18.7% of patients with MIS-C presented with an acute abdomen 50 . Even though the presentation of both MIS-C and acute appendicitis may be similar 51 , however, the treatment modality is different MIS-C patients usually receive nonoperative management, while patients with acute appendicitis require appendectomy 35 , 47 , 50 . Yock-Corrales et al .…”
Section: Challenges To the Treatment Of Pediatric Appendicitis During...mentioning
confidence: 99%
“…Prior infection or contact with a positive SARS-CoV-2 case and lack of an alternative diagnosis are among the criteria for establishing a diagnosis of MIS-C [85]. MIS-C abdominal pain can be severe and can mimic appendicitis [84,86,87]. MIS-C can also manifest with severe gastrointestinal diagnoses including appendicitis [88].…”
Section: Covid-19-positive Pediatric Patients With Suspected Appendic...mentioning
confidence: 99%